SPINAL ANAESTHESIA IN PAEDIATRIC PATIENTS UNDERGOING SURGERY OF SUB UMBILICAL REGION OF THE BODY - Jamil, Muhammad; Khan, Zar; Abbasi, Masroor Manshad; Ahmad, Khurshid (Journal of Ayub Medical College Abbottabad, 2011)
Background: The use of spinal anaesthesia in infants and children requiring surgeries of sub umbilical region is gaining considerable popularity worldwide. But in our setups in South Asia, this technique has not gained popularity yet. The objective of this prospective study was to evaluate the haemodynamic and respiratory safety of spinal anaesthesia in infants and children. Methods: In our study, 66 paediatric patients of age ranging from 6 months to 10 years of either sex, ASA I and II, undergoing surgeries of sub umbilical regions were included. Spinal anaesthesia was administered with Quincke 25 gauge needles at L3-L4 and L4-L5 space in the lateral decubitus position after premedication. Mean Arterial Blood Pressure (MAP), Heart rate, Spo2, duration of surgery and attempts of spinal block were the data recorded. Results: Out of the 66 patients, intra-operative Mean Arterial Blood Pressure (MAP) was normal in 65 (98.5%) of the patients. Heart rate was increased in 57 (86.4%) patients, intra operatively. Pulse oximetery was normal during surgery in all the children. Duration of surgery was less than one hour in 48 (72.7%) patients and it was between 1-2 hours in 18 (27.3%) of the patients. Feasibility in the form of attempts was first in 37 patients and second in 29 patients. Conclusion: The ease of performance and the safety regarding cardio- respiratory functions makes spinal anaesthesia as an alternative to general anaesthesia in infants and children undergoing surgeries of sub umbilical regions. Keywords: spinal anaesthesia, infants, sub umbilical, surgery, haemodynamics